Strategic Admission Management for Madrasah Competitiveness: Integrating Service Quality and School Branding - Yetty Faridatul Ulfah; Slamet Riadi; Suyanto Suyanto; Nur Amin; Rara Intan Mutiara Fajrin; Ari Agung Purnomo (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the optimisation strategies of New Student Admission (NSA) management at MTs Muhammadiyah Blimbing Sukoharjo through a service excellence and school branding approach. In an increasingly competitive educational landscape, institutions are required not only to provide quality learning but also to build a strong public image. This research employed a qualitative case study conducted from February to June 2025, with data collected through interviews, observations, and documentation. The findings indicate that the school implements service strategies such as one-stop services, digital-based information systems, and responsive communication, while branding strategies are carried out through social media promotion, showcasing institutional excellence via events, and publishing student achievements. The integration of these strategies effectively enhances public trust and expands the reach of prospective students both locally and beyond. Supporting factors include strong collaboration between management and teachers, as well as continuous service innovation. This study contributes to Islamic Education Management by offering a strategic model that integrates service quality and branding to strengthen institutional competitiveness. However, the study is limited to a single institutional context. Future research is recommended to include multiple institutions, apply quantitative methods, and conduct longitudinal studies, as well as explore digital leadership and educational innovation to better understand the sustainability of admission strategies in the digital era.